Robust time‐varying formation design for multiagent systems with disturbances: Extended‐state‐observer method. (1st March 2020) - Wang, Le; Xi, Jianxiang; He, Ming; Liu, Guangbin
Summary: Robust time‐varying formation design problems for second‐order multiagent systems subjected to external disturbances are investigated. First, by constructing an extended state observer, the disturbance compensation is estimated, which is a critical term in the proposed robust time‐varying formation control protocol. Then, an explicit expression of the formation center function is determined and impacts of disturbance compensations on the formation center function are presented. With the formation feasibility conditions, robust time‐varying formation design criteria are derived to determine the gain matrix of the formation control protocol by utilizing the algebraic Riccati equation technique. Furthermore, the tracking performance and the robustness property of multiagent systems are analyzed. Finally, the numerical simulation is provided to illustrate the effectiveness of theoretical results.